IMPLEMENTASI DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PADA FASHION UMKM MELALUI PLATFROM MARKET PLACE - Rifki Icha Amalia (PUTRA JAWA PUBLISHER, 2023)
Small and Medium Enterprises (MSMEs) participate in the convection business in the city of Surabaya. MSMEs that are important for this area have been organized in the city of Surabaya for quite a long time, that is, you could say more than 5 years. However, the practice of advertising is highly neglected and commonplace. Therefore, MSMEs in designing must be given preparation about the importance of taking advantage of advanced promotions, because in today's era it is more sophisticated and modern so that the advertising framework becomes more developed so that it can expand the reach of its business targets and can increase sales targets that are far superior. In addition, MSMEs are also given special assistance to ideally create a business account on digitization media. With the development of information technology infrastructure, it has triggered internet users so that another world view appears in business processes, especially by using the web and data innovation foundations. Business processes are assisted through web data innovation media that utilize virtual space as an activity position known as e-commerce so as to create an electronic market, namely the marketplace. In trade centers, every MSME actor can display his goods that are available for purchase without the need to create a framework. MSMEs are very productive because they make work easier. Organizations only need to provide total data about the goods they sell in the commercial center such as item data, costs, shipping, etc